Honeys with anti-inflammatory capacity can alter the elderly gut microbiota in an ex vivo gut model - Wu, Daoyan (2022)
The anti-inflammatory effect of different sourced honeys and the impact on elderly gut microbiota were studied in terms of chemical compositions, anti-inflammatory effect and gut microbiota modulating capacities. All four honeys suppressed the production of pro-inflammatory markers NO, IL-1β and IL-6 induced by lipopolysaccharide and promoted the expression of anti-inflammatory cytokines IL-10 in RAW 264.7 cells. Moreover, in the ex vivo batch gut model using elderly fecal microbiota (referred to as microcosm), it was showed that the addition of honeys increased the abundance of beneficial lactobacilli, decreased the abundance of potentially harmful Gram negative enteric bacteria, and exerted a beneficial effect on the production of short chain fatty acids. The concentration of gallic acid in honeys was positively correlated with the expression level of IL-10 and the abundance of lactobacilli. These findings indicate honeys with anti-inflammatory capacity have great potential for regulating the elderly gut microbiota which would lead to health benefits.